2017
DOI: 10.1590/0102-4698162221
|View full text |Cite
|
Sign up to set email alerts
|

A Desespecialização Do Trabalho Docente No México: Reflexões Sobre as Experiências De Eja E De Educação Profissional

Abstract: RESUMO: O presente artigo aborda as novas formas de trabalho docente no contexto da Educação de Jovens e Adultos (EJA) e da educação profissional do México, apontando suas relações com as reformas educacionais e a ascensão de modelos educativos baseados na centralização, na meritocracia, em competências, metas e resultados. As reflexões propostas baseiam-se em pesquisas realizadas em 2014 e 2015, no Distrito Federal e em cinco estados mexicanos, nas quais foram entrevistados docentes, estudantes e equipes técn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…The correlations between Mexico and Brazil in the field of technical and professional education have been the object of our research since 2014. In our studies (Silva, 2014, 2017, 2018a, 2018b, 2019; Silva and Riboli, 2016), we have found out that both countries have suffered great influence from the proposals of international organizations, which, in turn, have not imposed their educational perspectives from the top down. They have acted through partnership with national institutions to implement their proposals.…”
Section: Relations Between Brazil and Mexicomentioning
confidence: 81%
See 2 more Smart Citations
“…The correlations between Mexico and Brazil in the field of technical and professional education have been the object of our research since 2014. In our studies (Silva, 2014, 2017, 2018a, 2018b, 2019; Silva and Riboli, 2016), we have found out that both countries have suffered great influence from the proposals of international organizations, which, in turn, have not imposed their educational perspectives from the top down. They have acted through partnership with national institutions to implement their proposals.…”
Section: Relations Between Brazil and Mexicomentioning
confidence: 81%
“…As for education providers, CONALEP has the largest offer of technical and vocational courses in Mexico, with more than 300,000 students across the country. As Silva (2017) shows, CONALEP has great capillarity and centrality in Mexico, being spread across all states, attending to young and adult students. Most CONALEP centers, called Planteles, are located in impoverished and conflictive regions, increasing for this reason, the importance of this institution in that As can be seen from Figure 2, the CINTERFOR/ILO Network articulates public and private institutions in both Brazil and Mexico.…”
Section: The Cinterfor/ilo Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Por fim, deixo aqui meu abraço caloroso a cada leitor(a) que, certamente, fará excelente uso deste seleto florilégio acadêmico-científico. (2017); Kazales (2017);Ciavatta Franco (2000); Goergen (1991Goergen ( , 2014; Ibarrola (2020);Lourenço Filho and Monarcha (2004); Pietro and Egido (2014); Ruth and Leyva (2003); Schriewer (1993); Suassuna (2008). It was provisionally concluded that Mexican Professional Education -to the detriment of German Technical Education -should encompass a general and broad education, integrated with citizenship rights.…”
Section: Apresentaçãomentioning
confidence: 99%
“…Na literatura educacional, nas últimas duas décadas, o trabalho docente é tema recorrente, tendo como foco: condições de sua realização (OLIVEIRA, 2004;SHIROMA;LIMA-FILHO, 2011;LANTHEAUME, 2012;SILVA, 2017;TUNDIS et al, 2018;MELO, 2018);desenvolvimento profissional (JACOMINI;PENNA, 2016;OLIVEIRA;NUNES, 2017;BAROLLI et al, 2019); problemas relacionado à remuneração (ALVES; PINTO, 2011;BARBOSA, 2011); desprestígio profissional (LAPO; BUENO, 2003); saúde dos profissionais, tanto em âmbito nacional (BARROS; LOUZADA, 2007; ARAÚJO; CARVALHO, 2009;LEITE, 2011;PIZZIO;KLEIN, 2015;MOURA et al, 2019) Além disso, as pesquisas também discutem questões atreladas à identidade e aos saberes docentes (TEIXEIRA, 2007;MOLINA-NETO, 2010;MOURAZ, 2015;MESQUITA, 2020a); participação política e sindical do magistério (GENTILI et al, 2004;FERREIRA, 2007); autonomia profissional (TENTI-FANFANI, 2007; BARROS; AZEVEDO, 2016); discussões sobre gênero e trabalho do magistério (VIANNA, 2002;FERREIRA, 2004;DURÃES, 2012;CARVALHO et al, 2018); o papel da pesquisa nas práticas docentes (ABDALLA, 2005;TARDIF;ZOURHLAL, 2005); conexões do trabalho com a formação docente (BARRETTO, 2010;NASCIMENTO;REIS, 2017;PUGLIESE, 2017;…”
Section: Trabalho Docente Na Literaturaunclassified